Dlaczego uczniowie nie lubią szkoły? Osobowościowe uwarunkowania stosunku do szkoły zielonogórskich gimnazjalistów = Why don`t students like school? Personality factors of attitude to school represented by lower secondary school students in Zielona Góra - Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Students are the objects at school. Lower secondary school (gimnazjum) is a new type of school which is estimated in various ways. The article shows the variety of students` attitudes to their schools. During the research the students` attitude to their school obligations and how they feel at school were empirically studied. The article also presents determinants of lower secondary school students` attitude to their own schools.
Keywords: Zielona Góra; szkolnictwo ponadpodstawowe; uczniowie gimnazjów; badania